PENODAAN AGAMA DI INDONESIA: PROBLEMATIKA REGULASI DAN PERAN KEPOLISIAN - Said Anna Fauza; Muhammad Hadin Muhjad; Muslimah Hayati (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
In the era of modernization at this time, the intersection of religious life in Indonesia often experiences friction and violations of blasphemy or blasphemy. This research is to find out and analyze regulations related to the crime of blasphemy in the written positive law in Indonesia and the procedures of the Police in handling non-criminal blasphemy.The type of research used in this study is normative legal research. The results of the research: First: The regulation of the crime of blasphemy or hate speech against religion through internet media whose offense is listed in the Electronic Information and Transaction Law is part of the offense of blasphemy regulated in the provisions of Article 156a of the Criminal Code so that perpetrators who meet the elements as referred to in the Criminal Code, if it is carried out through internet media, can be subject to the provisions of speech hatred against religion as stipulated in Article 27A and Article 28 paragraph (2) of the Electronic Information and Transaction Law. Second: Handling of blasphemy crimes by the Police which is the implementation of the criminal investigation function which has now also been established The Directorate of Cyber Crimes (Dittipidsiber) is a work unit under the Criminal Investigation Branch of the National Police and is tasked with enforcing the law against cybercrime with stages in handling blasphemy crimes on the basis of reporting and/or complaints from a person or the community or based on information reports Preceded by an investigation and investigation plan, an investigation and investigation plan.